2011
DOI: 10.1149/1.3615938
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam Assisted Patterning and Dry Etching of Nafion Membranes

Abstract: We have successfully demonstrated the patterning of Nafion membranes for multiple electrochemical applications using electron beam lithography and dry etching strategies. The fabricated structures include arrays of lines and circles with features as small as 300 nm. The fidelity of the patterned profiles showed a dependency on resist baking temperature, masking layer thickness, and feature size. The propagation of cracks on a patterned Nafion substrate due to relaxation of stresses caused by the vacuum and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Blanket plasma etching on an unpatterned surface in comparison to other lithographic processes is a one‐step process that can be easily adopted for large area patterning. Currently, several etching methods have been investigated for restructuring the Nafion surface, but unlike previous work, here we explore the performance of Nafion membranes etched in a purely oxygenated plasma environment to take advantage of enhanced etch rates .…”
Section: Introductionmentioning
confidence: 99%
“…Blanket plasma etching on an unpatterned surface in comparison to other lithographic processes is a one‐step process that can be easily adopted for large area patterning. Currently, several etching methods have been investigated for restructuring the Nafion surface, but unlike previous work, here we explore the performance of Nafion membranes etched in a purely oxygenated plasma environment to take advantage of enhanced etch rates .…”
Section: Introductionmentioning
confidence: 99%
“…Developed by DuPont, it is a perfluorosulfonate ion exchange polymer wherein hydrophilic perfluorinated ether side chains end with sulphonate groups, which are periodically attached to hydrophobic perfluoroethylene backbone molecules. Nafion films have been extensively used in fuel cell [25] as well as in electrochemical [26] and optical sensors. For humidity sensing, Nafion is usually used as a matrix for casting films doped with different dyes in which RH is determined according to their spectrophotometric properties [14,[27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies seem to indicate that the patterning of PEM enhances the fuel cell performance, especially with the use of different techniques to generate a surface -patterning structure. These include surface roughening by abrasion [7], by the introduction of a rough transition Nafion thin film [8,9], by plasma treatments [10][11][12][13][14] and by the use of (optic, electronic) lithography [15][16][17][18][19][20][21]. One of the first attempts to pattern the surface of a Nafion membrane was made in 2002 by O'Hayre et al [7] who abraded the membrane by using SiC sandpaper to obtain fine and coarse roughening.…”
Section: Introductionmentioning
confidence: 99%
“…This transfer technique has been also used to transfer patterns from two micrometric stainless steel meshes on both sides of a Nafion N115 membrane [19]. To avoid the need for a mold, Omosebi et al [20,21] demonstrated the patterning of persulfonic Nafion membranes using electron beam lithography coupled with dry etching.…”
Section: Introductionmentioning
confidence: 99%